2017
DOI: 10.1186/s12885-017-3053-7
|View full text |Cite
|
Sign up to set email alerts
|

High expression of micro RNA-135A in hepatocellular carcinoma is associated with recurrence within 12 months after resection

Abstract: BackgroundHepatocellular carcinoma has a dismal prognosis due to recurrence rates of up to 70% after curative resection. Early recurrence is driven by synchronous microscopic intrahepatic metastases. The predictive value of histological parameters is discussed controversially and adjuvant therapy is not established. The aim of this study was to identify patients at high risk for early intrahepatic recurrence by expression profiling of selected micro RNAs.MethodsIn 52 patients undergoing HCC resection between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“… 27 Previous studies discovered that miR-135a expression is higher in cancer tissues such as hepatocellular carcinoma and colorectal cancer, facilitating cancer growth and invasion, and may serve as a biomarker. 31 , 32 Another study indicated that activating β-catenin was related to BC progression. 33 Consistent with the results of this study, mRNA and protein expression in cyclinD1 were shown to be upregulated in urothelial carcinoma of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Previous studies discovered that miR-135a expression is higher in cancer tissues such as hepatocellular carcinoma and colorectal cancer, facilitating cancer growth and invasion, and may serve as a biomarker. 31 , 32 Another study indicated that activating β-catenin was related to BC progression. 33 Consistent with the results of this study, mRNA and protein expression in cyclinD1 were shown to be upregulated in urothelial carcinoma of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, identifying new biomarkers for assessment of tumor aggressiveness 31 and predicting post-LT outcome is of critical importance in future research. DCP (des-gamma-carboxyprothrombin) 32 and selected noncoding RNAs (microRNAs and long noncoding RNAs) 33 hold promise and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-218 has been shown to decrease tumor growth (5), miR-26a to inhibit metastasis (6) and miR-214 to prevent angiogenesis (7) in HCC. Moreover, certain miRNAs, including miR-155 (8), miR-137 (9) and miR-135a (10) have been shown to be associated with the recurrence of and poor survival in HCC. Hence, miRNAs have the potential to act as biomarkers of and therapeutic targets in HCC.…”
Section: Introductionmentioning
confidence: 99%